Analisis Semiotika Komunikasi terhadap Interpretasi Pesan Motivasi dan Resiliensi dalam Lirik Lagu “Tapi” Band Perunggu - Nada Salsabila Setiawan; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Song lyrics as part of popular culture not only serve as entertainment, but also serve as a medium for conveying social, psychological, and life values. One of the themes that often emerge in contemporary music is the experience of migration and resilience in facing the pressures of urban life. This study aims to uncover the construction of the meaning of motivation and resilience in the lyrics of the song "Tapi" by Perunggu through Roland Barthes's semiotic approach. The study uses a descriptive qualitative method with Barthes's two-stage semiotic analysis that includes denotation, connotation, and myth. Primary data is in the form of song lyrics, while supporting data is obtained through interviews with listeners to strengthen the interpretation of the resulting meaning. The results show that at the denotative level, the lyrics represent the concrete experience of a migrant who leaves his hometown and faces the demands of adaptation in a new environment. At the connotative level, the experience is interpreted as an emotional journey supported by the symbol of a mother's prayer as a representation of protection, moral support, and a source of resilience. Meanwhile, at the mythical level, the lyrics naturalize the cultural ideology of fortitude, hard work, and responsibility as ideal values ​​inherent in the identity of migrants in Indonesian society. These findings indicate that the song "Tapi" not only reflects personal experiences but also reproduces social values ​​that shape people's perspectives on life's struggles. This research contributes to the development of the semiotics of popular music, particularly in understanding the relationship between spiritual symbols, resilience, and the construction of cultural meaning in song lyrics.